Left Ventricular Global Function Index and the Impact of its Companion Metric - Diaz-Navarro, Rienzi A.; Kerkhof, Peter L. M. (Frontiers in Cardiovascular Medicine, 2021)
Left ventricular (LV) global function index (LVGFI) has been introduced as a volume-based composite metric for evaluation of ventricular function. The definition formula combines stroke volume (SV), end-systolic volume (ESV), end-diastolic volume (EDV) and LV mass/density. Being a dimensionless ratio, this new metric has serious limitations which require evaluation at a mathematical and clinical level. Using CMRI in 96 patients we studied LV volumes, various derived metrics and global longitudinal strain (GLS) in order to further characterize LVGFI in three diagnostic groups: acute myocarditis, takotsubo cardiomyopathy and acute myocardial infarction. We also considered the LVGFI companion (C), derived from the quadratic mean. Additional metrics such as ejection fraction (EF), myocardial contraction fraction (MCF) and ventriculo-arterial coupling (VAC), along with their companions (MCFC and VACC) were calculated. All companion metrics (EFC, LVGFIC, MCFC, and VACC) showed sex-specific differences, not clearly reflected by the corresponding ratio-based metrics. LVGFI is mathematically coupled to both EF (with R = 0.86) and VAC (R = 0.87), which observation clarifies why these metrics not only share similar prognostic values but also identical shortcomings. We found that the newly introduced LVGFIC has incremental value compared to the single use of LVGFI, EF, or GLS, when characterizing the three patient groups.